Pure and Applied Biogeography - Hufnagel, Levente (IntechOpen, 2018)
This book, Pure and Applied Biogeography, gives a very interesting report and overview about the frontiers of such parts of recent biogeographical research, which plays important roles in solving our most pressing global problems (biodiversity crisis, climate change, water issues, and sustainable agriculture). Our book consists of three sections: "Introduction", "Pure Biogeography and Global Patterns" and "Applied Biogeography and Regional Issues." After the introductory chapter, which is about the main branches and aims of biogeography in service of solving global problems, - we can find three chapters as parts of the first section. First chapter in this section is in close relation with the origin of biodiversity and conservation. The second and third chapters are about the biogeograhical aspects of climate change and biodiversity. In the second section of this book three applied biogeographical chapters can be found, which are related to agriculture, theoretical background of biological plant protection against herbivores, and regional patterns in ecological biogeography.